Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan pada CV Nusa Indah 10 di Kota Solok - Ida Nirwana; Arfimasri Arfimasri; Putri Anggraini (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This research seeks to assess the impact of Leadership Style and Work Discipline on Employee Performance at CV Nusa Indah 10 located in Solok City, utilizing a sample of 32 respondents and adopting quantitative methods. The sampling technique employed is Total Sampling. Data collection was carried out through the distribution of a questionnaire. Multiple regression analysis revealed the equation for the variables Leadership Style and Work Discipline's effect on Employee Performance to be Y = 12.024 + 0.220 X1 + 0.482 X2 + e. The t-test indicated that Leadership Style (X1) significantly affects Employee Performance, as demonstrated by a t-count of 2.201, which is greater than the t-table value of 2.04523, with a significance level of 0.036, which is less than 0.05. Consequently, Ha was accepted while H0 was rejected. Additionally, Work Discipline (X2) significantly influences Employee Performance, with a t-count of 5.409 surpassing the t-table value of 2.04523, and a significance level of 0.000, which is also below 0.05. This led to the acceptance of Ha and rejection of H0. The F test results showed that both Leadership Style and Work Discipline jointly affect Employee Performance, with an f count of 51.591 exceeding the f table value of 3.33, and a significance level of 0.000, which is under 0.05. Furthermore, the R Square value obtained is 0.781, indicating that Leadership Style and Work Discipline collectively account for 78.1% of the variance in Employee Performance at CV Nusa Indah 10 in Solok City, with the remaining variance attributed to other factors not examined in this study.